(untitled) (Педагогіка вищої та середньої школи, 2012)
У статті розглядаються питання освіти як національної цінності у спадщині вітчизняних та зарубіжних філософів, педагогів. Визначено місце освіти у розвитку педагогічної науки. Ключові слова: освіта, національні цінності, вітчизняні педагоги, розвиток педагогічної науки. The paper considers subjects of education as the national value in heritage of native and foreign philosophers, educationalists. The place of education in development of pedagogical science is determined. Key words: education, national values, native educationalists, the development of pedagogical science.